Soft magnetic composite material coated with nano metal oxide insulating material and preparation method of soft magnetic composite material

By mixing metal soft magnetic powder and nanometal oxide insulating material in the rotating blade device to form core-shell composite powder, annealing and pressing forming, the problem of complex and long time in the prior art is solved, and the high magnetic permeability and low loss characteristics of the soft magnetic composite material are achieved, which is suitable for large-scale production.

CN119517596AActive Publication Date: 2025-02-25CENT SOUTH UNIV

Patent Information

Application Number
CN202411697504.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the prior art, the method of coating metal magnetic powder is relatively complex, the process time is long, and the bonding strength of the cladding layer and the base metal is difficult to ensure, resulting in unstable magnetic properties of the soft magnetic composite material and increasing the production cost.

Method used

The rotating blade device is used to mix the metal soft magnetic powder and the nanometal oxide insulating material to form a core-shell composite powder, which is then annealed and pressed. Finally, annealed heat treatment is performed under a protective atmosphere to prepare a soft magnetic composite material coated with nanometal oxide insulating material.

Benefits of technology

The nano-metal oxide insulating material is uniformly distributed on the surface of metal soft magnetic powder, with strong binding force and controllable coating thickness. The prepared soft magnetic composite material has high magnetic permeability and low loss, mild process conditions and simple equipment, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517596A_ABST
    Figure CN119517596A_ABST
Patent Text Reader

Abstract

The invention discloses a nano metal oxide insulating material coated soft magnetic composite material and a preparation method thereof, and the preparation method comprises the following steps: (1) putting metal soft magnetic powder and a nano metal oxide insulating material into a steel cylinder equipped with a rotating blade, and rotating the blade to drive the raw material to flow to obtain core-shell composite powder; (2) carrying out annealing treatment on the core-shell type composite powder to obtain a precursor; and (3) mixing the precursor and a lubricant, then pressing the mixture into a green body, and carrying out annealing heat treatment on the green body in a protective atmosphere to obtain the soft magnetic composite material. The prepared soft magnetic composite material is uniform in insulating layer and high in coverage rate, the binding force between the nano metal oxide and the metal soft magnetic matrix is high, the thickness of the coating layer is controllable, the obtained soft magnetic composite material has high magnetic conductivity and lower loss, and the insulating coating method is mild in process condition, simple in equipment, short in coating treatment time, high in efficiency, low in cost and suitable for industrial production. The method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic materials, in particular to a soft magnetic composite material coated with a nano metal oxide insulating material and a preparation method thereof. Background Art

[0002] Metal soft magnetic composite materials are made of metal magnetic powders that are coated with insulating materials and then formed and heat treated. They are also called metal magnetic powder cores. They have high magnetic permeability, low loss and high DC bias characteristics. They are used as the core part of reactors, transformers, converters, inductors and motor stators, and are widely used in power supplies, motors and other fields.

[0003] The metal magnetic powders used as soft magnetic composite materials include Fe, FeSi, FeSiAl, FeNi, FeNiMo, amorphous nanocrystalline soft magnetic materials, etc., and the insulating materials include organic, inorganic, and organic-inorganic mixtures. Organic materials are easy to coat evenly, but they are easy to decompose and have insufficient heat resistance, which affects the magnetic properties of soft magnetic composite materials. Inorganic materials are divided into phosphates, oxides, and ferrites. Among them, phosphates will decompose at 500°C, so the heat resistance is not high. Ferrites need to be treated in an oxidizing atmosphere, which is different from the treatment requirements of metal soft magnetic materials in a reducing or neutral atmosphere, so it is difficult to adjust the performance to achieve the best. Oxides are currently widely used because of their high insulation, good temperature stability, and low requirements for the atmosphere. In particular, nano-metal oxides are widely used because of their fine particles, uniform coating, controllable thickness, and good insulation.

[0004] There is extensive research and application on how nano-metal oxides can achieve insulation coating on metal magnetic powders. Chinese invention patent 201910702030X uses epoxy resin to organically insulate metal magnetic powder, and then uses silane coupling agent to modify and couple the nano-silicon oxide powder generated by hydrolysis of epoxy resin and ethyl orthosilicate, thereby achieving composite insulation of metal magnetic powder by epoxy resin and silicon oxide. Chinese invention patent 2020113331544 uses nano-SiO2 and organic solvent, silicone resin and silane coupling agent coating replenisher to soak FeSi, FeSiAl, FeNi and other magnetic powder cores after heat treatment to improve magnetic properties. Chinese invention patent 2023111726270 uses silicon source, oleic acid, acidulant and heating on the surface of FeSiAl powder to generate the first layer of SiO2 insulation layer, and then adds aluminum source and alkali solution and heats to react to generate the second layer of Al2O3 insulation layer.

[0005] Although the above invention patents use the method of generating nano-oxides by reaction or directly using nano-oxides for coating treatment to achieve the coating effect, the process is relatively complicated, the process time is long, and it is difficult to control. In addition, the bonding strength between the coating layer and the base metal is difficult to ensure, which affects the magnetic stability of the soft magnetic composite material and increases the preparation cost. Summary of the invention

[0006] The purpose of the present invention is to provide a soft magnetic composite material coated with a nano-metal oxide insulating material and a preparation method thereof, so as to solve the problems that the method for coating the above-mentioned metal magnetic powder is relatively complicated, the process time is long, the bonding strength between the coating layer and the base metal is difficult to ensure, and the magnetic properties of the obtained soft magnetic composite material are unstable.

[0007] To achieve the above object, the first aspect of the present invention provides a method for preparing a soft magnetic composite material coated with a nano metal oxide insulating material, comprising the following steps:

[0008] (1) placing metal soft magnetic powder and nano metal oxide insulating material into a steel cylinder equipped with rotating blades, the blades rotate to drive the raw materials to flow, and obtain a core-shell composite powder;

[0009] (2) annealing the core-shell composite powder to obtain a precursor;

[0010] (3) The precursor and the lubricant are mixed and then pressed into a green body. The green body is annealed and heat treated in a protective atmosphere to obtain a soft magnetic composite material.

[0011] Preferably, in step (1), the metal soft magnetic powder includes one or more of FeSi, FeSiAl, FeNi, FeNiMo, FeSiB amorphous, FeCuNbSiB nanocrystalline; the nano metal oxide insulating material includes one or more of SiO2, Al2O3, TiO2, MgO, kaolin, and clay.

[0012] Preferably, in step (1), the average particle size of the metal soft magnetic powder is 5 μm to 200 μm, and the average particle size of the nano metal oxide insulating material is 2 nm to 200 nm.

[0013] Preferably, in step (1), the mass ratio of the nano metal oxide insulating material to the metal soft magnetic powder is (0.2-5): (99.8-95).

[0014] Preferably, in step (1), the blades rotate at a speed of 3000 to 8000 rpm, resulting in a linear speed of 20 to 30 m / s, and a processing time of 2 to 10 min.

[0015] Preferably, in step (2), the annealing temperature is 200-600° C., the time is 20-60 min, and the atmosphere is argon or nitrogen.

[0016] Preferably, in step (3), the lubricant comprises one or both of zinc stearate and lithium stearate, and the amount of the lubricant added is 0.2 wt.% to 1.2 wt.% of the precursor;

[0017] Silane coupling agent and organic resin are also added to the precursor, the amount of silane coupling agent added is 0-0.5wt.% of the precursor, and the organic resin is one or two of silicone resin and epoxy resin, and the amount of organic resin added is 0-1.0wt.% of the precursor.

[0018] Preferably, in step (3), the amount of the silane coupling agent added is 0.03-0.5 wt.% of the precursor, and the amount of the organic resin added is 0.06-1.0 wt.% of the precursor.

[0019] Preferably, in step (3), the pressing pressure is 800 to 2200 MPa, and the holding time is 0 to 5 s.

[0020] Preferably, in step (3), the annealing heat treatment temperature is 400-800° C., the holding time is 30-120 min, and the protective atmosphere is argon, nitrogen, or a mixture of the two.

[0021] The second aspect of the present invention provides a soft magnetic composite material coated with nano metal oxide insulating material, which is prepared by the above-mentioned preparation method.

[0022] Preferably, the nano-metal oxide insulating material in the soft magnetic composite material is uniformly adhered to the surface of the metal soft magnetic powder to form a core-shell composite material in which the nano-metal oxide insulating material covers the metal soft magnetic powder.

[0023] Therefore, the soft magnetic composite material coated with the nano-metal oxide insulating material of the above structure and the preparation method of the present invention have the following beneficial effects:

[0024] (1) The nano-metal oxide insulating material in the soft magnetic composite material prepared by the present invention is evenly distributed on the surface of the metal soft magnetic powder with a high coverage rate. The bonding force between the nano-metal oxide insulating material and the metal soft magnetic powder is strong, and the coating thickness is controllable. The prepared soft magnetic composite material has high magnetic permeability and lower loss.

[0025] (2) The insulation coating method of the present invention has mild process conditions, simple equipment, short coating treatment time, high efficiency, low cost, and is suitable for large-scale production.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the SEM image of the atomized FeSiAl raw powder particles;

[0028] Figure 2 This is the EDS image of the element distribution of the atomized FeSiAl raw powder particles;

[0029] Figure 3 This is a SEM image of FeSiAl composite powder particles coated with a nano-SiO2 insulating layer in Example 1;

[0030] Figure 4 This is the EDS diagram of element distribution of FeSiAl composite powder particles coated with nano-SiO2 insulating layer in Example 1. DETAILED DESCRIPTION

[0031] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0032] Example 1

[0033] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0034] FeSiAl powder was prepared by atomization method. The SEM morphology and EDS spectrum of the powder are shown in Figure 1 and Figure 2 500 g of FeSiAl powder with a particle size of 30 μm was weighed and slowly placed in a stainless steel cylinder equipped with a fast rotating blade, and then 0.5 wt.% (2.5 g) of SiO2 powder with a particle size of 20 nm was also placed in the cylinder, and the rotating blade was turned on and the speed was adjusted to 5000 r / min. After mixing for 5 minutes, FeSiAl@SiO2 coated powder was obtained. The SEM image and EDS spectrum are shown in Figure 3 and Figure 4 The stainless steel cylinder equipped with fast rotating blades used in the present invention is a device that has been disclosed in the prior art, the equipment name is a high-efficiency fusion coating machine, the manufacturer is Wuxi Taixian Powder Technology Co., Ltd., and the equipment model is VSH-0.3.

[0035] The process of preparing FeSiAl powder by atomization method in this embodiment is as follows:

[0036] The Fe, Si and Al single substances with the composition of Fe-9.6Si-5.4Al are placed in a vacuum induction melting furnace, melted at 1500°C, and then sprayed with nitrogen to make powder.

[0037] Table 1 Content of each element in the atomized FeSiAl raw powder particles

[0038]

[0039] Table 2 Element contents of FeSiAl@SiO2 coated powder

[0040]

[0041] Subsequently, the FeSiAl@SiO2 coated powder was placed in a tubular furnace and kept at 400°C for 30 minutes under argon for treatment. Then, 0.4wt.% of KH550 was added to the annealed FeSiAl@SiO2 coated powder and stirred evenly, and then 0.8wt.% of silicone resin was added and stirred evenly to obtain the final coated powder.

[0042] The silicone resin is a high temperature resistant silicone resin, produced by Hubei Xinsihai Chemical Co., Ltd., model number 9603.

[0043] 0.5wt.% zinc stearate lubricant was added to the coated powder and mixed evenly, and the powder was pressed into a ring-shaped compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 2000MPa; the ring-shaped compact was heat treated in an Ar atmosphere for 50min at a heat treatment temperature of 700°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSiAl@SiO2 soft magnetic composite material.

[0044] Example 2

[0045] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0046] FeSi powder was prepared by atomization method. 500 g of FeSi powder with a particle size of 32 μm was weighed and slowly placed into a stainless steel cylinder equipped with fast rotating blades. Then 0.7 wt.% (3.5 g) of SiO2 powder with a particle size of 10 nm was also placed in the cylinder, and the rotating blades were turned on and the speed was adjusted to 6000 r / min. After mixing for 4 minutes, FeSi@SiO2 coated powder was obtained.

[0047] The process of preparing FeSiAl powder by atomization method in this embodiment is as follows:

[0048] The Fe and Si single substances with a composition of Fe-5.5Si are placed in a vacuum induction melting furnace, melted at 1500°C, and then powdered by spraying with nitrogen.

[0049] The FeSi@SiO2 coated powder was then placed in a tube furnace and kept at 450°C for 20 minutes under argon. 0.5wt.% KH550 was added to the annealed FeSi@SiO2 coated powder and stirred evenly, and then 1.0wt.% of organic silicone resin was added and stirred evenly to obtain the final coated powder.

[0050] 0.6wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into an annular compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 1800MPa; the annular compact was heat treated in an Ar atmosphere for 40min at a heat treatment temperature of 720°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSi@SiO2 soft magnetic composite material.

[0051] Example 3

[0052] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0053] FeSiAl powder was prepared by atomization method. 500 g of FeSiAl powder with a particle size of 18 μm was weighed and slowly placed in a stainless steel cylinder equipped with a fast rotating blade. Then 0.8 wt.% (4.0 g) of Al2O3 powder with a particle size of 60 nm was also placed in the cylinder, and the rotating blade was turned on. The speed was adjusted to 5600 r / min. After mixing for 6 minutes, FeSiAl@Al2O3 coated powder was obtained. The process of preparing FeSiAl powder by atomization method is the same as that in Example 1.

[0054] The FeSiAl@Al2O3 coated powder was then placed in a tube furnace and kept at 480°C for 35 minutes under argon. 0.35wt.% KH550 was added to the annealed FeSiAl@Al2O3 coated powder and stirred evenly, and then 0.7wt.% of silicone resin was added and stirred evenly to obtain the final coated powder.

[0055] 0.4wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into an annular compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 1900MPa; the annular compact was heat treated in an Ar atmosphere for 45min at a heat treatment temperature of 680°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSiAl@Al2O3 soft magnetic composite material.

[0056] Example 4

[0057] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0058] FeSi powder was prepared by atomization method. 500 g of FeSi powder with a particle size of 52 μm was weighed and slowly placed in a stainless steel cylinder equipped with a fast rotating blade. Then 1.0 wt.% (5.0 g) of Al2O3 powder with a particle size of 30 nm was also placed in the cylinder, and the rotating blade was turned on. The speed was adjusted to 6500 r / min. After mixing for 4.5 min, FeSi@Al2O3 coated powder was obtained. The preparation method of FeSi powder was the same as that of Example 2.

[0059] The FeSi@Al2O3 coated powder was then placed in a tube furnace and kept at 500°C for 25 minutes under argon. 0.45wt.% KH550 was added to the annealed FeSi@Al2O3 coated powder and stirred evenly, and then 0.9wt.% of organic silicone resin was added and stirred evenly to obtain the final coated powder.

[0060] 0.5wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into a ring-shaped compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 1900MPa; the ring-shaped compact was heat treated in an Ar atmosphere for 30min at a heat treatment temperature of 740°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSi@Al2O3 soft magnetic composite material.

[0061] Comparative Example 1

[0062] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0063] FeSiAl powder was prepared by atomization method. 500 g of FeSiAl powder with a particle size of 30 μm was weighed and slowly put into a mixer. Then 0.5 wt.% (2.5 g) of SiO2 powder with a particle size of 20 nm was also put into the mixer. A small amount of steel balls were added. The ball-to-powder weight ratio was 1:1. The mixer speed was 150 r / min. After mixing for 360 min, FeSiAl@SiO2 coated powder was obtained. The preparation method of FeSiAl powder was the same as that in Example 1.

[0064] The FeSiAl@SiO2 coated powder was then placed in a tube furnace and kept at 400°C for 30 minutes under argon. 0.4wt.% KH550 was added to the annealed FeSiAl@SiO2 coated powder and stirred evenly, and then 0.8wt.% of silicone resin was added and stirred evenly to obtain the final coated powder.

[0065] 0.5wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into an annular compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 2000MPa; the annular compact was heat treated in an Ar atmosphere for 50min at a heat treatment temperature of 700°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSiAl@SiO2 soft magnetic composite material.

[0066] Comparative Example 2

[0067] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0068] FeSi powder was prepared by atomization method. 500g of FeSi powder with a particle size of 32μm was weighed and slowly put into the mixer. Then 1.0wt.% (5.0g) of Al2O3 powder with a particle size of 10nm was also put into the mixer. A small amount of steel balls were added. The ball-to-material weight ratio was 1:1. The mixer speed was 120r / min. After mixing for 390min, FeSi@Al2O3 coated powder was obtained. Subsequently, the FeSi@Al2O3 coated powder was placed in a tubular furnace and kept at 500℃ for 25min under argon for treatment. Then 0.45wt.% of KH550 was added to the annealed FeSi@Al2O3 coated powder and stirred evenly. Then 0.9wt.% of silicone resin was added and stirred evenly to obtain the final coated powder.

[0069] 0.5wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into a ring-shaped compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 1900MPa; the ring-shaped compact was heat treated in an Ar atmosphere for 30min at a heat treatment temperature of 740°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSi@Al2O3 soft magnetic composite material.

[0070] Comparative Example 3

[0071] The method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material comprises the following steps:

[0072] FeSiAl powder was prepared by atomization method (preparation method was the same as that in Example 1), 500g of FeSiAl powder with a particle size of 18μm was weighed and slowly put into a mixer, then 3.0wt.% (15.0g) of aluminum sol was also put into the mixer, a small amount of steel balls were put in, the ball-to-material weight ratio was 1:1, the mixer speed was 120r / min, and after mixing for 280min, aluminum sol-coated FeSiAl powder was obtained. Subsequently, the aluminum sol-coated FeSiAl powder was placed in a tubular furnace and kept at 800℃ for 30min under argon for treatment. During the heat treatment, the aluminum sol was first converted into aluminum gel and finally converted into Al2O3 to be uniformly coated on the surface of FeSiAl. Then, 0.5wt.% of KH550 was added to the heat-treated FeSiAl@Al2O3 coated powder and stirred evenly, and then 1.0wt.% of organic silicone resin was added and stirred evenly to obtain the final coated powder.

[0073] 0.5wt.% zinc stearate lubricant was added to the coated composite powder and mixed evenly, and pressed into a ring-shaped compact (outer diameter 27mm*inner diameter 15mm*height 11mm) at a pressure of 2000MPa; the ring-shaped compact was heat treated in an Ar atmosphere for 40min at a heat treatment temperature of 680°C; and then cooled to room temperature with the furnace (ventilation was maintained during the process of cooling to room temperature with the furnace (to prevent the sample from being oxidized)) to obtain a FeSiAl@Al2O3 soft magnetic composite material.

[0074] Performance Testing

[0075] The FeSiAl and FeSi soft magnetic composite materials samples prepared in Examples 1 to 4, the FeSiAl soft magnetic composite materials prepared in Comparative Example 1, the FeSi soft magnetic composite materials prepared in Comparative Example 2, and the material samples prepared in Comparative Example 3 were tested for magnetic permeability and magnetic loss using a SY-8218 AC BH analyzer. The properties of the obtained samples are shown in Table 3 (B max =50mT).

[0076] Table 3 Properties of composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0077]

[0078]

[0079] From Table 3 above, we can see that:

[0080] Compared with the existing FeSiAl soft magnetic composite material (prepared in Comparative Example 1), the FeSiAl soft magnetic composite material sample prepared in Example 1 has better magnetic permeability and frequency characteristics. With the increase of frequency, the magnetic permeability has better stability; it has smaller magnetic loss at high frequency; and the DC bias is equivalent; the process cycle adopted is shorter / more efficient.

[0081] Compared with the existing FeSi soft magnetic composite material (prepared in Comparative Example 2), the FeSi soft magnetic composite material sample prepared in Example 2 has better magnetic permeability and frequency characteristics. With the increase of frequency, the magnetic permeability has better stability; it has smaller magnetic loss under high frequency; and the DC bias is equivalent; the process cycle adopted is shorter / more efficient.

[0082] Compared with the existing FeSiAl soft magnetic composite material (prepared in Comparative Example 3), the FeSiAl soft magnetic composite material sample prepared in Example 3 has better magnetic permeability and frequency characteristics. With the increase of frequency, the magnetic permeability has better stability; it has smaller magnetic loss at high frequency; and the DC bias is equivalent; the process cycle adopted is shorter / more efficient.

[0083] Compared with the existing FeSi soft magnetic composite material (prepared in Comparative Example 2), the FeSi soft magnetic composite material sample prepared in Example 4 has better magnetic permeability and frequency characteristics. With the increase of frequency, the magnetic permeability has better stability; it has smaller magnetic loss at high frequency; and the DC bias is equivalent; the process cycle adopted is shorter / more efficient.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a soft magnetic composite material coated with a nano-metal oxide insulating material, characterized in that: The following steps are involved: (1) Putting metal soft magnetic powder and nano-metal oxide insulating material into a steel cylinder equipped with rotating blades, the rotation of the blades drives the raw materials to flow, and a core-shell composite powder is obtained; (2) annealing the core-shell composite powder to obtain a precursor; (3) The precursor and the lubricant are mixed and then pressed into a green body. The green body is annealed and heat treated under a protective atmosphere to obtain a soft magnetic composite material.

2. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (1), the metal soft magnetic powder includes one or more of FeSi, FeSiAl, FeNi, FeNiMo, FeSiB amorphous, FeCuNbSiB nanocrystalline; the nano metal oxide insulating material includes one or more of SiO2, Al2O3, TiO2, MgO, kaolin, and clay.

3. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (1), the average particle size of the metal soft magnetic powder is 5 μm to 200 μm, and the average particle size of the nano metal oxide insulating material is 2 nm to 200 nm.

4. The method for preparing the soft magnetic composite material coated with nano-metal oxide insulating material according to claim 1, characterized in that: In step (1), the mass ratio of the nano metal oxide insulating material to the metal soft magnetic powder is (0.2~5):(99.8~95).

5. The method for preparing the soft magnetic composite material coated with nano-metal oxide insulating material according to claim 1, characterized in that: In step (1), the blade rotates at a speed of 3000-8000 rpm, resulting in a linear speed of 20-30 m / s and a processing time of 2-10 min.

6. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (2), the annealing temperature is 200-600°C, the time is 20-60 min, and the atmosphere is argon or nitrogen.

7. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (3), the lubricant includes one or both of zinc stearate and lithium stearate, and the amount of the lubricant added is 0.2wt.% to 1.2wt.% of the precursor; A silane coupling agent and an organic resin are also added to the precursor, wherein the amount of the silane coupling agent added is 0-0.5 wt.% of the precursor; the organic resin is one or both of silicone resin and epoxy resin, and the amount of the organic resin added is 0-1.0 wt.% of the precursor.

8. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (3), the pressing pressure is 800~2200MPa, and the holding time is 0~5s.

9. The method for preparing the soft magnetic composite material coated with nano metal oxide insulating material according to claim 1, characterized in that: In step (3), the annealing heat treatment temperature is 400-800°C, the holding time is 30-120 min, and the protective atmosphere is argon, nitrogen or a mixture of the two.

10. A soft magnetic composite material coated with nano-metal oxide insulating material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance low-loss compound magnetic powder core and preparation method thereof

    CN106041061A

  • FeSiNi soft magnetic composite material and preparation method thereof

    CN117393261A

  • FeSi soft magnetic composite material

    CN118231079A

Cited By

  • Soft magnetic composite material with low loss and high direct current bias and preparation method and application thereof

    CN120452982A

  • Soft magnetic composite material, preparation method thereof and magnetic element

    CN121331638A

  • High-performance FeSiAl magnetic powder core and preparation method and application thereof

    CN121687716A

  • Composite insulation coated metal soft magnetic powder, coating method and application

    CN121709409A

  • Method for synchronously realizing high saturation magnetization intensity, high effective magnetic conductivity and low coercive force of magnetic powder core

    CN122599227A